(untitled) (Research, Society and Development, 2021)
Bibliometric indicators are useful for assessing the impact of academic productivity, coupled with geopopulation understanding. The aim of this study was to analyze the spatial distribution of Biotechnology research in Brazil, verifying a possible correlation between the h-index and social development. The sample consisted of data from 959 professors and 59 stricto sensu biotechnology programs in the country. Self-referenced data for each program outlined their descriptive profiles. Local distribution and autocorrelation maps (MoranMap) of the programs and the h-index by population density were built. Bivariate analysis (LISA) considered dependent variables (program rate and h-index for population density) and independent (MHDI). As a result, there was a prevalence of academic doctoral programs, with longer creation time, workload, CAPES score, number of teachers and average h-index, with most programs in the Southeast Region, except academic master’s degrees, in the Northeast. The distribution of programs by population density was higher in RIAUs in Palmas, Araraquara and Alfenas, while the h-index in RIAUs in Palmas, Belo Horizonte and Rio de Janeiro. There was positive autocorrelation of programs clustered in RIAUs in SP and Porto Alegre and between programs and h-index in RIAUs in Porto Alegre, Caxias do Sul and Ribeirão Preto. Bivariate analysis MHDI-programs showed high-high clusters in RIAUs of SP and Porto Alegre and MHDI-h-index high-high clusters in RIAUs of SP, MG and RJ. The mapping of the h-index and MHDI helped to understand the academic productivity of Biotechnology in Brazil, contributing to the discussion of evaluation models in unequal realities in the national scenario.